CORRELATION BETWEEN STRATUM CORNEUM HYDRATION ON NON LESIONAL SKIN AREA AND SEVERITY OF ATOPIC DERMATITIS - , MARIA SERAPHINE AGUSTA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Atopic dermatitis (AD) is a chronic, itchy, inflammatory skin disease occurs most commonly during early infancy and childhood and has many kind of manifestation. Many factors can lead to atopic dermatitis. One of them is degradation of skin barrier function and one of the parameter is the stratum corneum hydration. So far, there is no research done to know whether stratum corneum hydration on non lesional skin area will affect the severity of atopic dermatitis or not in Yogyakarta, Indonesia. Objective : The objective of the study is to know the correlation between stratum corneum hydration on non lesional skin area measured by corneometer with severity of atopic dermatitis measured by objective SCORAD index. Methodology : The method used in this study is analytic cross sectional measuring stratum corneum hydration on non lesional skin area using corneometer and severity of atopic dermatitis using Objective SCORAD Index, the result is measured using Spearmanâs Rho correlation test. The population that are used here are atopic dermatitis patients who came to the Dermatology and Venereology Policlinic in dr. Sardjito Hospital on April-September 2012. Result : Statistic test using Spearmanâs Rho test method shows that there is no correlation between stratum corneum hydration on non lesional skin area with the severity of atopic dermatitis. Summary : There is no correlation between stratum corneum hydration on non lesional skin area and severity of atopic dermatitis.